(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Environmentally, friendly businesses at this time are needed to suppress existing environmental problems. Companies must market environmentally, friendly products so as not to add to environmental problems. The purpose of this study is to analyze the influence of green products, green advertising, green knowledge on purchasing decisions with brand image as an intervening variable. This study used a quantitative type of research. Data collection techniques using questionnaires. data analysis techniques using SEM PLS. The results show that green products, green advertising, green knowledge have a significant influence on consumer financing decisions. Brand image is also an intervening variable that indirectly influences green products, green advertising, green knowledge on purchasing decisions